2002
DOI: 10.1246/cl.2003.28
|View full text |Cite
|
Sign up to set email alerts
|

Application of Carbon Nanotubes to Counter Electrodes of Dye-sensitized Solar Cells

Abstract: In order to search for an efficient counter electrode in a dye-sensitized solar cells, three kinds of nano-carbon materials were examined. When single wall carbon nanotubes (SWCNTs) were used as a carbon electrode, the conversion efficiency of the cells is 4.5%. This value is comparable to Grätzel-type dye-sensitized solar cell (counter electrode: platiun-suputtered fluorine-doped tin oxide) under the same experimental condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
248
2
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(267 citation statements)
references
References 10 publications
4
248
2
5
Order By: Relevance
“…Individual Carbon nanotubes (CNTs) have some extraordinary properties such as ultrahigh electrical and thermal conductivity [6,7], light weight and high mechanical strength [8], which make them promising for various applications, including solar energy [9], electronics [10], and biomedical technology [11]. However, these excellent properties often drastically diminish in macroscopic form, e.g., films, sheets, fibers, ropes, wires, and cables of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Individual Carbon nanotubes (CNTs) have some extraordinary properties such as ultrahigh electrical and thermal conductivity [6,7], light weight and high mechanical strength [8], which make them promising for various applications, including solar energy [9], electronics [10], and biomedical technology [11]. However, these excellent properties often drastically diminish in macroscopic form, e.g., films, sheets, fibers, ropes, wires, and cables of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…SWCNT can be of benefit in several ways. Firstly there has been some evidence that carbon nanotubes can replace platinum as a catalyst because of their high surface area and electronic properties [6][7][8]. However, these SWCNTs are also of interest because they can also act as photosensitive elements themselves [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The same authors reported also a cell with catalyst layer made of Polymeric material such as PEDOT. Saito et al and Suzuki et al reported the application of a chemically produced conducting polymer and carbon nanotubes used as counterelectrode (Saito et al, 2002;Suzuki et al, 2003;Saito et al, 2004). Although the fabrication cost can be decreased in these cases, the conversion efficiency is still relatively low compared to a cell with a Pt based counter-electrode.…”
Section: Dye Solar Cells Fabricationmentioning
confidence: 99%